2020
DOI: 10.1002/ecy.3026
|View full text |Cite
|
Sign up to set email alerts
|

The role of omnivory in mediating metacommunity robustness to habitat destruction

Abstract: Citation: Liao, J., D. Bearup, and W. F. Fagan. 2020. The role of omnivory in mediating metacommunity robustness to habitat destruction. Ecology 101(6):Abstract. Omnivores have long been known to play an important role in determining the stability of ecological communities. Recent theoretical studies have suggested that they may also increase the resilience of their communities to habitat destruction, one of the major drivers of species extinctions globally. However, these outcomes were obtained for minimal fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 69 publications
1
11
1
Order By: Relevance
“…1b). By affecting species persistence and species diversity (Hiebeler 2000, Liao et al 2013a, b2013b, 2016, 2017a, b2017b, 2020), the configuration of habitat can affect also the ‘invasibility' of the native community (i.e. more diverse native communities should be more resistant to invasions: diversity–invasibility hypothesis; Elton 1958).…”
Section: Introductionmentioning
confidence: 99%
“…1b). By affecting species persistence and species diversity (Hiebeler 2000, Liao et al 2013a, b2013b, 2016, 2017a, b2017b, 2020), the configuration of habitat can affect also the ‘invasibility' of the native community (i.e. more diverse native communities should be more resistant to invasions: diversity–invasibility hypothesis; Elton 1958).…”
Section: Introductionmentioning
confidence: 99%
“…For occupancy, we were able to mirror our experimental results with simulations by tuning the extinction function in our model. Previous studies (Gilarranz & Bascompte, 2012;Liao et al, 2020) showed that occupancy patterns in networks with different degrees of heterogeneity can vary with extinction rates. They demonstrated that in scenarios of low extinction/ colonization, random networks will have higher occupancy than scale-free networks, a trend that is reversed as extinction probability increases.…”
Section: Discussionmentioning
confidence: 98%
“…A general approach to MC structure and dynamics requires that it accommodates its most recognized feature -competition cf. (Leibold et al 2004;Logue et al 2011;Thompson et al 2020), other direct interactions such as predation (Abrams 2007;Jabot & Bascompte 2012;Ryberg et al 2012;Vanschoenwinkel et al 2013;Haegeman & Loreau 2014;Liao et al 2020), mutualism (Yu et al 2004), parasitism, commensalism as well as a high number of possible indirect interactions (e.g., Miller & Kneitel 2005;Gravel et al 2010;Miller & terHorst 2012).…”
Section: Species Interactionsmentioning
confidence: 99%